PENGARUH PEMBERIAN LEV AMISOL PRA VAKSINASI AVIAN INFLUENZA (Al) TERHADAP RESPON KEBAL AYAM PETELUR - Lili Zalizar (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2009)
Success of vaccination to certain diseases depends of immune response condition. One of drug that can act as immunomodulator is levamisol. The purpose of the reseach was to find out effect  of levamisol  pre AI vaccination  to immune  response  of layer. The research  used  experimental   method  and was based  on Randomized   Completely  Design. One  hundred   and  fifty   Days   Old  Chicks   (DOC)   were   divided   into  three  goups   of treatments.  First goup was without  levamisole  (control goup).The  second  and third goup were  given  levamisol   at  1  mg/50  kg  body  weight  respetively  for   three  and  six  days, respectively.    Lymphocyte    cell   was   evaluated    between   two   to  five  weeks   after   Al vaccination.   Leucocyte   cells  like monocyte  and  neutrophyl   (heterophyl)   were  examined two days after Al vaccination.Result  of the  research  showed  that levamisole  treatment  pre  AI  vaccination  can highly  significant   increase  non  specific immune  response  with  remarkable   increase  in monocyte  cells.  But its effect to total of neutrophyle  cells did not significant.  Levamisole treatment  pre  Al  vaccination   Al  can  also  highly  significant   increase   celluler  specific immune  response  indicating  by a remarkable  increase  in lymphocyte   cells. Based  of the result,   it  is  concluded   to  necessarily   use  levamisole  pre  Al   vaccination   to  increase immune response  in chickens  against Al natural  infection  (JIIPB  2009 Vol 19 No 1:  10-19)Keywords   :  levamisole,  vaccination,  immune response,  layer